COMPETENCY BASED LANGUAGE TEACHING: THEORY AND GUIDANCE FOR CLASSROOM PRACTICES - Rambe, Sojuangon (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2013)
AbstractCBLT is application of CBA in field of language teaching. This approach has been widely used in many parts of the world as framework for teaching language for adults, vocational schools and private corporations. In spite of being widely used and supported by many linguists and practitioners, this approach also faces many critiques mainly in the aspects of material development and activities to develop them.Generally this approach is to develop language performances which are useful in the real world either for daily use or work settings. This method does not specify any learning theory to attain the competency, views language as life skills, develops the four language skills depend on the requirement of the competencies, employs communication activities in the real world as learning materials, and conducts evaluation in the form of continual assessment of performance by facing the students performance to its ideal features to be successfully conducted in the real world.Â Key Words: competency, performance, life skill, standard, language